2012 IEEE Nuclear Science Symposium and Medical Imaging Conference Record (NSS/MIC) 2012
DOI: 10.1109/nssmic.2012.6551725
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity improvement of time-of-flight (ToF)-PET detector through recovery of Compton scattered annihilation photons

Abstract: In PET detector designs, the scintillator material can be partitioned such that a block of crystals share timin g /ener g y readout electronics. A fraction of the incident 511 keY photons produce simultaneous events in two adjacent block readouts due to Compton scatterin g followed by escape from the primary block. These inter-block Compton scatter events are typically not processed in current PET scanners. We have used radiation transport simulations to determine the fraction of inter-block Compton events for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In terms of validating the GATE MC simulations, the simulated NEMA sensitivity values, presented in Tables 1 , 3 , were in line with the expected, theoretical values for all simulated PET radioisotopes, These theoretical values were based on the measured GE Signa PET/MR sensitivity for 18 F while accounting for the differences in branching ratio between each isotope and 18 F. These sensitivity values confirmed the higher count rate and increased sensitivity ( Iagaru et al, 2019 ) of the GE Signa PET system due several design factors including Compton scatter recovery, longer axial FOV and reduced ring diameter ( Lubberink and Herzog, 2011 ; Wagadarikar et al, 2014 ; Hsu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…In terms of validating the GATE MC simulations, the simulated NEMA sensitivity values, presented in Tables 1 , 3 , were in line with the expected, theoretical values for all simulated PET radioisotopes, These theoretical values were based on the measured GE Signa PET/MR sensitivity for 18 F while accounting for the differences in branching ratio between each isotope and 18 F. These sensitivity values confirmed the higher count rate and increased sensitivity ( Iagaru et al, 2019 ) of the GE Signa PET system due several design factors including Compton scatter recovery, longer axial FOV and reduced ring diameter ( Lubberink and Herzog, 2011 ; Wagadarikar et al, 2014 ; Hsu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…This design also reduces the amount of PET-attenuating material in the PET field of view, contributing in part to the reduced activity requirements. The use of scatter recovery techniques additionally supports this advantage as well [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…A recent study has evaluated the advantage of the implementation of such recovery procedures by using the inter-block Compton scatter on TOF-PET scanners. It was found that this setup is expected to result in an overall scanner sensitivity improvement of up to 20% without significant processing overhead [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recovering triple coincidences has been proposed as another approach for sensitivity increase . Typically in PET imaging, a pair of 511‐keV annihilation photons are coincidently detected and a (LOR) is drawn.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we compared different recovery schemes that are expected to be efficient for small ‐ animal PET geometry and relatively simple for real implementation . An accurate recovery scheme has to be applied to correctly find the true LORs of the IDS events . Finally, the effects of the PET system properties, including energy resolution and DOI capabilities on the performance of IDS recovery methods were explored.…”
Section: Introductionmentioning
confidence: 99%